Utilizing Linear Regression for Predicting Sales of Top-Performing Products - Pratama, matthew (Jejaring Penelitian dan Pengabdian Masyarakat, 2023)
PT Ajidarma Delta Medika is a company engaged in the sale of medical devices in the city of Bekasi. This company markets a variety of medical device products. Judging from the large number of consumer requests for medical device products based on sales data for the last 3 years, predictions are needed for the best-selling product sales, in order to facilitate the company in planning the supply of stock. To find out the best-selling medical device product sales, data prediction techniques are used with the Linear Regression algorithm. By using the Linear Regression algorithm, the results are obtained to predict the best-selling sales of several products sold at PT Ajidarma Delta Medika. This research produces an accuracy value with the MAPE formula for predicting the best-selling product sales of 14.2%. This shows that the linear regression method is good at predicting sales of medical devices in the following year.